Preparation method of low-volatility and high-toughening-efficiency toughening agent for nylon
During the preparation of the nylon toughening agent, silicon oil is filled into the second polymer, the gap between the molecular chains is increased, and the reaction between maleic anhydride and unsaturated chemical bonds is promoted, which solves the problems of high odor, high volatility and low toughening efficiency of the existing nylon toughening agent, and achieves the preparation of toughening agents with low volatility and high toughening efficiency.
Patent Information
- Application Number
- CN202311230817.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-03-25
AI Technical Summary
The existing nylon toughening agents have problems such as high odor, high volatility and low toughening efficiency, which limits the application scenarios of modified nylon materials.
A method for preparing a toughener for nylon with low volatility and high toughening efficiency is adopted. By adding a second polymer and silicone oil to a high-speed mixer for oil filling treatment, the gap between the molecular chains is increased, the reaction between maleic anhydride and unsaturated chemical bonds is promoted, and the content of free maleic anhydride is reduced.
It significantly improves the odorability and toughening efficiency of toughener, reduces volatility, and improves the application scenarios of the product.
Smart Images

Figure CN119684541A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer composite materials, and in particular to a method for preparing a toughening agent for nylon with low volatility and high toughening efficiency. Background Art
[0002] With the continuous development of science and technology, polymer material modification and alloying technology has been widely used. In order to better meet the needs of different customers, the technical requirements of polymer toughening agent products have been challenged.
[0003] The toughening modification of nylon has been an important topic of nylon modification since the 1970s. The United States, Western Europe, and Japan have successively developed various grades of high-impact nylon alloys. Nylon is a resin that is relatively easy to form alloys, and a suitable compatibilizer is the key to forming tough nylon. Ethylene-α-octene copolymer (POE) is a new polyolefin thermoplastic elastomer using constrained geometry metallocene catalyst technology, and ethylene propylene diene monomer (EPDM) is a terpolymer of ethylene, propylene, and non-conjugated dienes. Nylon and POE or EPDM can complement each other and obtain the required performance. However, nylon and ethylene-α-octene grafted copolymers POE and EPDM are incompatible systems, while POE grafted maleic anhydride or EPDM grafted maleic anhydride can significantly improve the compatibility and interfacial adhesion between nylon and POE or EPDM. Conventional nylon toughening agents have the problems of strong odor, high volatility, and low toughening efficiency, which limits the application scenarios of modified nylon materials.
[0004] The performance advantages of polypropylene are: low density, high rigidity and hardness, wide source of raw materials, easy processing and molding; the product has excellent comprehensive performance. Polypropylene has good compatibility with ethylene-α-octene copolymer. It is a worthy research topic to use polypropylene blended with ethylene-α-octene copolymer or EPDM rubber as grafting raw materials. The current toughening agents have problems such as low grafting rate and strong odor. Most manufacturers mainly increase the grafting rate by increasing the amount of maleic anhydride and initiator or adding small molecular compounds such as styrene. Although this method can also obtain grafted polypropylene with a higher grafting rate, there are still problems such as strong odor and yellowish appearance of the grafted polymer, and small molecular compounds such as styrene are volatile, flammable and explosive, and have harsh storage conditions.
[0005] Chinese invention patent application CN104628971A discloses an ultra-tough polypropylene blended ethylene-α-octene graft copolymer and a preparation method thereof. The ultra-tough polypropylene blended ethylene-α-octene graft copolymer comprises the following components in parts by weight: 10 to 40 parts of polypropylene, 90 to 60 parts of ethylene-α-octene copolymer, 1 to 3 parts of maleic anhydride, 0.1 to 1 part of initiator and 0.5 to 1 part of liquid additive; the preparation method of the ultra-tough polypropylene blended ethylene-α-octene graft copolymer comprises: putting the raw materials into a high-speed mixer and mixing for 5 to 10 minutes, adding them into a twin-screw extruder after metering through the main feed, reacting for 1 to 2 minutes, and obtaining the product through pulling, cooling, and pelletizing.
[0006] However, although the patent solves the problem of low grafting rate of maleic anhydride, the liquid additives and initiators used will introduce new small molecules with odor, increase the content of odor molecules in the toughening agent, and the odor problem and flammability are not solved. After being put into production, there is a risk of harm to the health of workers and there are also hidden dangers in environmental protection and safety.
[0007] Therefore, there is an urgent need to provide a method for preparing a nylon toughening agent with low odor, low volatility and high toughening efficiency to solve the above-mentioned problems. Summary of the invention
[0008] The present invention aims to solve the problem that the maleic anhydride grafting rate in the prior art toughening agent is low while the free maleic anhydride is relatively high, or other new small molecules are introduced to increase the maleic anhydride grafting rate, which leads to the problem that the toughening agent has strong volatility and strong odor. Therefore, a preparation method of a toughening agent for nylon with low volatility and high toughening efficiency is proposed.
[0009] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows: A method for preparing a nylon toughening agent with low volatility and high toughening efficiency comprises the following steps: 1) Add the second polymer and silicone oil in a high-speed mixer in proportion, mix for 3-5 minutes at a mixing rate of 1000-1300 rpm, take out and seal, and let stand at room temperature for 12h-24h to obtain the oil-filled second polymer for standby use; 2) Add initiator and lubricant in proportion in a high-speed mixer, mix for 1-2 minutes at a mixing rate of 1000-1300 rpm, take out the mixed material and set aside; 3) Add polyolefin elastomer, polypropylene, the oil-extended second polymer obtained in step 1) and maleic anhydride in a high-speed mixer in proportion, mix for 1-3 minutes, and gradually add the mixed material in step 2) at a mixing rate of 1000-1300 rpm; 4) The material obtained in step 3) is put into a twin-screw extruder, and the temperature of each zone of the extruder is set as follows: zone 1 160-190°C, zone 2 190-230°C, zone 3 190-230°C, zone 4 190-230°C, zone 5 190-230°C, zone 6 190-230°C, zone 7 170-200°C, zone 8 160-190°C, zone 9 150-180°C, zone 10 150-180°C, zone 11 160-190°C, zone 12 160-190°C, zone 13 160-190°C, die head 180-210°C; the main engine speed is 100-300 r / min; feeding frequency is 100-200kg / h; cooling water temperature is 20-50℃; during the melt extrusion process, vacuum is drawn in the tenth and eleventh zones; the extruder screw aspect ratio is 30-60; antioxidant is added in the ninth zone of melt extrusion; The amounts of the raw materials in parts by weight are as follows: Polyolefin elastomer: 60-90 parts; Polypropylene: 10-30 parts; Maleic anhydride: 0.5-3.0 parts; Initiator: 0.5-3.0 parts; Second polymer: 1.0-10.0 parts; Antioxidant: 0.1-0.5 parts; Lubricant: 0.1-1.0 parts; The silicone oil is dimethyl silicone oil, and the weight ratio of the dimethyl silicone oil to the second polymer is 0.2-1:1; the viscosity of the dimethyl silicone oil is 100-1000mm 2 / s.
[0010] The polyolefin elastomer is one or a mixture of ethylene-α-octene copolymer (POE) and ethylene propylene diene monomer (EPDM); the polyolefin elastomer has the characteristics of outstanding low-temperature impact resistance, high elasticity, low specific gravity and excellent electrical insulation performance, and is widely used for toughening and modifying other polymers.
[0011] The second polymer is styrene-isoprene-styrene block copolymer (SIS); SIS has the characteristics of high temperature plasticity, good low temperature resistance, good elasticity and good solubility resistance, and contains more unsaturated chemical bond structures in the molecular chain. Compared with styrene-butadiene-styrene block copolymer (SBS), SIS has the advantages of fluidity, compatibility with other materials and good aging resistance.
[0012] The initiator is di-(tert-butylperoxyisopropyl)benzene (BIPB). When the traditional initiator diisopropyl peroxide (DCP) initiates a grafting reaction, the isopropylphenoxy free radicals generated after the peroxide bond breaks can also form methyl free radicals and acetophenone. Acetophenone is a substance with an unpleasant odor and is harmful to the human body. BIPB maintains an initiation effect similar to that of DCP without producing odorous byproducts, which is conducive to the preparation of a low-volatile toughening agent.
[0013] The antioxidant is a 1:1 mixture of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1010) and tris[2.4-di-tert-butylphenyl] phosphite (antioxidant 168); antioxidant 1010 and antioxidant 168 are antioxidant systems used in conventional polyolefin materials. After being introduced into the ninth extrusion zone, the antioxidant system can effectively increase the aging probability of the toughening agent at the rear end of the extrusion and extend the storage period of the toughening agent.
[0014] The lubricant is zinc stearate; zinc stearate is a non-toxic, non-corrosive solid powder with the characteristics of high purity, transparency and good thermal stability. After being added to the system, zinc stearate can increase the brightness of the toughening agent, increase the dispersion uniformity of the components and reduce the production current, making it easier to produce.
[0015] The polypropylene is one or more of homopolymer polypropylene (PP-H), block copolymer polypropylene (PP-B) or random copolymer polypropylene (PP-R); pure polyolefin elastomer is difficult to be normally extruded and granulated due to its high melt viscosity, so it is necessary to add some polypropylene resin to improve the melt viscosity of the system to facilitate smooth production.
[0016] Beneficial effects of the present invention: 1. In the present invention, the second polymer is a thermoplastic elastomer containing unsaturated chemical bonds. When added to the reaction system, it will not reduce the toughening efficiency of the final product, and the unsaturated chemical bonds contained can react with free maleic anhydride in the system to reduce the maleic anhydride content and improve the odor.
[0017] 2. In the present invention, the second polymer is filled with silicone oil by stirring the second polymer and silicone oil evenly, then sealing and standing for more than 12 hours, so that the silicone oil molecules enter between the polymer molecular chains, increasing the gaps between the molecular chains, which is beneficial for the "contact" between maleic anhydride and the unsaturated chemical bonds in the second polymer molecular chains, reducing the content of free maleic anhydride molecules in the system and improving the odor, instead of directly mixing silicone oil with the raw materials in the traditional way, which only serves to bond the powdered raw materials to the surface of the granular raw materials.
[0018] 3. The traditional method of preparing nylon toughening agent is to add white oil (including paraffin oil and cyclohexane oil, etc.) or liquid ingredients such as silicone oil to the formula, which only serves to stick the powdered raw materials to the surface of the granular raw materials, thereby improving the mixing uniformity between the raw materials during the mixing and preparation process, but has no obvious effect on the odor and toughening efficiency of the nylon toughening agent; and because the main component of white oil is C16~C31 normal isoalkanes, which are not resistant to high temperatures, it is easy to undergo oxidation reactions during the preparation process, resulting in an increase in the content of odor molecules and a yellowish color, and interfering with the process of grafting maleic anhydride molecules to the molecular chains of polyolefin elastomers, which is not conducive to further improving the grafting rate and affecting the toughening efficiency and product appearance. At the same time, the main raw material of nylon toughening agent is polyolefin elastomer, and the free volume between the molecular chains is large, making it easier for small molecules such as odor molecules to volatilize and diffuse out, so the odor of nylon toughening agent is more sensitive to the content of odor molecules. The silicone oil used in the present invention is not only colorless, odorless, and non-yellowing, and will not affect the appearance and smell of the product, but also almost does not participate in the grafting reaction of maleic anhydride, and will not affect the toughening efficiency and appearance of the product.
[0019] 4. For SIS, white oil is usually filled as a plasticizer, which can not only increase the elasticity and toughness of the elastomer, but also has less heat-resistant precipitation; however, based on the above reasons, the present invention creatively fills silicone oil into styrene elastomer, not only because silicone oil is colorless, odorless and does not turn yellow, but also because silicone oil is filled into the second polymer, so that silicone oil molecules enter between polymer molecular chains, increasing the gaps between molecular chains, which is conducive to the "contact" of maleic anhydride with the unsaturated chemical bonds in the second polymer molecular chain, reducing the content of free maleic anhydride molecules in the system, and improving odor, instead of directly mixing silicone oil with raw materials in the traditional way, which only serves to bond the powdered raw materials to the surface of the granular raw materials.
[0020] 5. In the present invention, the second polymer is a thermoplastic elastomer containing unsaturated chemical bonds. When added to the reaction system, it will not reduce the toughening efficiency of the final product, and the unsaturated chemical bonds contained can react with free maleic anhydride in the system to reduce the maleic anhydride content and improve the odor.
[0021] 6. In the present invention, the preparation method of the nylon toughening agent is not the traditional one-step method, that is, after all the raw materials are mixed evenly, a grafting reaction is carried out using a twin-screw extruder or an internal mixer to prepare the toughening agent, but a two-step method is adopted, that is, first, silicone oil is filled into the second polymer, so that the silicone oil molecular components are inserted into the middle of the second polymer molecular chain, increasing the gap between the molecular chains, and then the oil-filled second polymer is mixed with other raw materials, and a twin-screw extruder is used for preparation to obtain a nylon elastomer. This method fully exposes the unsaturated chemical bonds in the second polymer molecular chain, and then reacts with excess maleic anhydride to reduce the content of free maleic anhydride molecules and improve the odor. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the infrared spectra of the toughening agent for nylon prepared in Group 1 of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0023] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] The present disclosure, including the relevant parameters or data in the embodiments, was obtained by the following test methods: In order to characterize the toughening efficiency of the product, 100g of sample and 1900g of PA6 YH800 were mixed evenly and put into a twin-screw extruder. The temperature of the twin-screw extruder was controlled at 220-240℃ to obtain toughened PA6; then the pellets were pulled and cut; finally, they were injection molded into standard test specimens for corresponding mechanical property tests.
[0025] 1. Appearance: Place the sample in a standard light box and visually observe the appearance and color of the sample.
[0026] 2. Grafting rate: 1) Dissolution / neutralization: Accurately weigh 0.5 g of the refined grafted material, place it in a 500 mL three-necked distillation flask, add 80 mL of xylene, and heat under reflux until the grafted material is completely dissolved; while still hot, use a pipette to add excess KOH-ethanol solution (denoted as V 1 ), heat under reflux for 30 minutes, cool to 50°C; open the glass stopper on one side of the three-necked flask, add two drops of phenolphthalein indicator, and cover with the glass stopper; during this process, no precipitate can be precipitated from the solution. If there is precipitate, heat and pyrolyze it.
[0027] 2) Titration: Place the three-necked flask in a water bath in a constant temperature magnetic stirrer, control the temperature at about 40°C, and start the rotor stirring; use HCl-isopropanol standard solution for constant temperature titration, stop titration when the solution turns pink, and record the volume V of the consumed HCl-isopropanol standard solution 2 .
[0028] The grafting rate was calculated according to the following formula: Where: C MAH,% is the grafting rate; m is the mass of the refined maleic anhydride grafted polyolefin elastomer; V 1 The volume of excess KOH-ethanol standard solution added for titration; C 1 is the concentration of KOH-ethanol standard solution; V 2 The volume of HCl-isopropanol standard solution required for titration; C 2 is the concentration of HCl-isopropanol standard solution; 98.06 is the molecular weight of maleic anhydride.
[0029] The titration experiment was repeated two to three times and the average value was calculated.
[0030] 3. Volatile matter: Taking advantage of the easy sublimation of maleic anhydride and the low water absorption rate of other raw materials, take 10-20g of sample and place it in a moisture analyzer to test the volatile matter content. The test conditions are 105℃, 10min.
[0031] 4. Odor level: Test according to the method specified in PV 3900.
[0032] 5. Mechanical properties: Tensile properties: According to GB / T 1040-2018, the tensile properties were tested on a universal material testing machine at a tensile rate of 10 mm / min at room temperature. Bending performance: According to the provisions of GB / T 9341-2008, the bending performance test was carried out on a universal material testing machine with a bending rate of 2 mm / min and room temperature; Izod notched impact strength: According to GB / T 1043-2008, the Izod notched impact strength test was carried out on an impact testing machine with a pendulum energy of 2.75 J at room temperature and -40°C.
[0033] Example 1 This embodiment provides a method for preparing a toughening agent for nylon with low volatility and high toughening efficiency. This embodiment is based on the types and amounts of raw materials in each group in Table 1 below: Table 1 Types and amounts of raw materials in each group in Example 1 The toughening agent is prepared by the following method: 1) Add the second polymer and silicone oil in a high-speed mixer according to the proportion, mix for 4 minutes at a mixing rate of 1300 rpm, take out and let stand for 24 hours to obtain the oil-filled second polymer for standby use; 2) Add initiator and lubricant in proportion in a high-speed mixer, mix for 2 minutes at a mixing rate of 1300 rpm, and take out for use; 3) adding polyolefin elastomer, polypropylene, the product obtained in step 1) and maleic anhydride in proportion in a high-speed mixer, mixing for 2 minutes, and gradually adding the product obtained in step 2) at a mixing rate of 1300 rpm; 4) The product obtained in step 3) is fed into a twin-screw extruder. In this embodiment, the temperature settings of each zone are as shown in Table 2, the main engine speed is 200 r / min; the feeding frequency is 150 kg / h; the cooling water temperature is 30°C; during the melt extrusion process, vacuum is drawn in the tenth and eleventh zones; the extruder screw aspect ratio is 50; and an antioxidant is added in the ninth zone of melt extrusion.
[0034] Table 2 Temperature settings of each zone of the extruder in Example 1 The performance test results of the toughening agent obtained by each group in this example are shown in Table 3 Table 3 New energy test results of each group in Example 1 Example 2 This embodiment provides a method for preparing a toughening agent for nylon with low volatility and high toughening efficiency. This embodiment is based on the types and amounts of raw materials in each group in Table 4 below: Table 4 Types and amounts of raw materials in each group in Example 2 The toughening agent is prepared by the following method: 1) Add the second polymer and silicone oil in a high-speed mixer according to the proportion, mix for 4 minutes at a mixing rate of 1200 rpm, take out and let stand for 12 hours to obtain the oil-filled second polymer for standby use; 2) Add initiator and lubricant in proportion in a high-speed mixer, mix for 2 minutes at a mixing rate of 1200 rpm, and take out for use; 3) adding polyolefin elastomer, polypropylene, the product obtained in step 1) and maleic anhydride in proportion in a high-speed mixer, mixing for 2 minutes, and gradually adding the product obtained in step 2) at a mixing rate of 1200 rpm; 4) The product obtained in step 3) is fed into a twin-screw extruder. In this embodiment, the temperature settings of each zone are as shown in Table 2, the main engine speed is 200 r / min; the feeding frequency is 150 kg / h; the cooling water temperature is 30°C; during the melt extrusion process, vacuum is drawn in the tenth and eleventh zones; the extruder screw aspect ratio is 50; and an antioxidant is added in the ninth zone of melt extrusion.
[0035] Table 5 Temperature settings of each zone of the extruder in Example 2 The performance test results of the toughening agent obtained by each group in this example are shown in Table 6.
[0036] Table 6 New energy test results of each group in Example 2 Example 3 This embodiment provides a method for preparing a toughening agent for nylon with low volatility and high toughening efficiency. This embodiment is based on the types and amounts of raw materials in each group in Table 7 below: Table 7 Types and amounts of raw materials in each group in Example 3 The toughening agent is prepared by the following method: 1) Add the second polymer and silicone oil in a high-speed mixer according to the proportion, mix for 5 minutes at a mixing rate of 1100 rpm, take out and let stand for 20 hours to obtain the oil-filled second polymer for standby use; 2) Add initiator and lubricant in proportion in a high-speed mixer, mix for 2 minutes at a mixing rate of 1100 rpm, and take out for use; 3) adding polyolefin elastomer, polypropylene, the product obtained in step 1) and maleic anhydride in proportion in a high-speed mixer, mixing for 3 minutes at a mixing rate of 1100 rpm, and gradually adding the product obtained in step 2); 4) The product obtained in step 3) is fed into a twin-screw extruder. The temperature settings of each zone in this embodiment are shown in Table 8, the main engine speed is 300 r / min; the feeding frequency is 200 kg / h; the cooling water temperature is 50°C; during the melt extrusion process, vacuum is drawn in the tenth and eleventh zones; the extruder screw aspect ratio is 60; and an antioxidant is added in the ninth zone of melt extrusion.
[0037] Table 8 Temperature settings of each zone of the extruder in Example 3 The performance test results of the toughening agent obtained by each group in this embodiment are shown in Table 9: Table 9 New energy test results of each group in Example 3 Comparative Example 1 This comparative example is a toughening agent prepared in Example 4 disclosed in the invention patent with publication number CN104628971A. The notched impact strength result of Example 4 in the comparative document is the optimal example. The performance testing method of the present invention is used to detect the performance of the toughening agent and verify the experimental results.
[0038] The raw materials and dosages in this comparative example are shown in Table 10: Table 10 Raw materials and dosage in Comparative Example 1 The performance test results of the toughening agent obtained in Comparative Example 1 are shown in Table 11.
[0039] Comparative Example 2 Compared with Group 1 in Example 1, the difference between this comparative example and Group 1 in Example 1 is that the silicone oil in the raw materials is deleted, and the other raw materials are the same as those in Group 1 in Example 1. The toughening agent in this comparative example was prepared by the following method: 1) Add initiator and lubricant in proportion in a high-speed mixer, mix for 2 minutes at a mixing rate of 1300 rpm, and take out for use; 2) adding polyolefin elastomer, polypropylene, second polymer and maleic anhydride in proportion in a high-speed mixer, mixing for 2 minutes, and gradually adding the product obtained in step 2) at a mixing rate of 1300 rpm; 3) The product obtained in step 3) is put into a twin-screw extruder. The temperature settings of each zone in this comparative example are shown in Table 2 and are the same as those in Example 1. The main engine speed is 200 r / min; the feeding frequency is 150 kg / h; the cooling water temperature is 30°C; during the melt extrusion process, vacuum is applied in the tenth and eleventh zones; the extruder screw aspect ratio is 50; and an antioxidant is added in the ninth zone of melt extrusion.
[0040] The performance test results of the toughening agent obtained in Comparative Example 2 are shown in Table 11.
[0041] Comparative Example 3 Compared with Group 1 in Example 1, this comparative example differs in that the silicone oil in the raw material is replaced with white oil, and the other raw materials are the same as those in Group 1 in Example 1. In this comparative example, the toughening agent was prepared by the same preparation method as in Example 1.
[0042] The performance test results of the toughening agent obtained in Comparative Example 3 are shown in Table 11.
[0043] Comparative Example 4 Compared with Group 1 in Example 1, this comparative example differs in that: The toughening agent described in this comparative example is prepared by the following method: 1) Add the second polymer and silicone oil in a high-speed mixer according to the proportion, mix for 4 minutes at a mixing rate of 900 rpm, take out and let stand for 10 hours to obtain the oil-filled second polymer for standby use; 2) Add initiator and lubricant in proportion in a high-speed mixer, mix for 2 minutes at a mixing rate of 900 rpm, and take out for use; 3) adding polyolefin elastomer, polypropylene, the product obtained in step 1) and maleic anhydride in proportion in a high-speed mixer, mixing for 2 minutes, and gradually adding the product obtained in step 2) at a mixing rate of 900 rpm; 4) The product obtained in step 3) is fed into a twin-screw extruder. In this embodiment, the temperature settings of each zone are as shown in Table 2, the main engine speed is 200 r / min; the feeding frequency is 150 kg / h; the cooling water temperature is 30°C; during the melt extrusion process, vacuum is drawn in the tenth and eleventh zones; the extruder screw aspect ratio is 50; and an antioxidant is added in the ninth zone of melt extrusion.
[0044] The performance test results of the toughening agent obtained in Comparative Example 4 are shown in Table 11.
[0045] Table 11 Comparative Examples 1-4 Performance Test Results of Tougheners As can be seen from Table 1-11, compared with Example 1, Comparative Example 1 has a yellowish appearance, a low grafting rate, a high volatile matter and a high odor level, and performs poorly, and the impact performance of toughened PA6 is even worse, indicating that the toughening agent prepared by the invention patent with publication number CN104628971A is obviously inferior to the present invention; Comparative Examples 2-4 also have deficiencies in appearance, grafting rate, volatile matter, odor level and impact performance of toughened nylon, indicating that adding silicone oil instead of using white oil, oil filling process, etc., all affect the final product quality. Comprehensively comparing the performance test results of Examples 1-3 and Comparative Examples 1-4, Examples 1-3 are more suitable for preparing maleic anhydride grafted polyolefin elastomers with low volatility and high toughening efficiency.
[0046] from Figure 1 It can be seen that both nylon toughening agents have infrared absorption peaks at 1720 cm-1, which is the infrared absorption peak of the CO bond, indicating that the maleic anhydride molecules are successfully grafted onto the molecular chain of the polyolefin elastomer after the melt extrusion process; however, the infrared peak of the first group of Example 1 of the present invention is more obvious, indicating that more maleic anhydride molecules are grafted onto the molecular chain of the polyolefin elastomer, and the grafting rate is higher.
[0047] In summary, after reading the present invention document, ordinary technicians in this field can make various other corresponding transformation schemes based on the technical scheme and technical concept of the present invention without creative mental labor, which all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a nylon toughening agent with low volatility and high toughening efficiency, characterized in that: The following steps are involved: 1) Add the second polymer and silicone oil in a high-speed mixer in proportion, mix for 3-5 minutes at a mixing rate of 1000-1300 rpm, take out and seal, and let stand at room temperature for more than 12h-24h to obtain the oil-filled second polymer for standby use; 2) Add initiator and lubricant in proportion in a high-speed mixer, mix for 1-2 minutes at a mixing rate of 1000-1300 rpm, take out the mixed material and set aside; 3) Add polyolefin elastomer, polypropylene, the oil-extended second polymer obtained in step 1) and maleic anhydride in a high-speed mixer in proportion, mix for 1-3 minutes, and gradually add the mixed material in step 2) at a mixing rate of 1000-1300 rpm; 4) The material obtained in step 3) is put into a twin-screw extruder, and the temperature of each zone of the extruder is set as follows: zone 1 160-190°C, zone 2 190-230°C, zone 3 190-230°C, zone 4 190-230°C, zone 5 190-230°C, zone 6 190-230°C, zone 7 170-200°C, zone 8 160-190°C, zone 9 150-180°C, zone 10 150-180°C, zone 11 160-190°C, zone 12 160-190°C, zone 13 160-190°C, die head 180-210°C; the main engine speed is 100-300 r / min; feeding frequency is 100-200kg / h; cooling water temperature is 20-50℃; during the melt extrusion process, vacuum is drawn in the tenth and eleventh zones; the extruder screw aspect ratio is 30-60; antioxidant is added in the ninth zone of melt extrusion; The amounts of the raw materials in parts by weight are as follows: Polyolefin elastomer: 60-90 parts; Polypropylene: 10-30 parts; Maleic anhydride: 0.5-3.0 parts; Initiator: 0.5-3.0 parts; Second polymer: 1.0-10.0 parts; Antioxidant: 0.1-0.5 parts; Lubricant: 0.1-1.0 parts; The silicone oil is dimethyl silicone oil, and the weight ratio of the dimethyl silicone oil to the second polymer is 0.2-1:
1.
2. The preparation method according to claim 1, characterized in that: The polyolefin elastomer is ethylene-α-octene copolymer or ethylene propylene diene monomer rubber, or a mixture of the two.
3. The preparation method according to claim 1, characterized in that: The initiator is di-(tert-butylperoxyisopropyl)benzene.
4. The preparation method according to claim 1, characterized in that: The antioxidant is a 1:1 mixture of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and tris[2,4-di-tert-butylphenyl]phosphite.
5. The preparation method according to claim 1, characterized in that: The lubricant is zinc stearate.
6. The preparation method according to claim 1, characterized in that: The polypropylene is one or more of homopolymer polypropylene, block copolymer polypropylene or random copolymer polypropylene.
7. The preparation method according to claim 1, characterized in that: The viscosity of the dimethyl silicone oil is 100-1000 mm 2 / s.
Citation Information
Patent Citations
Ultratough polypropylene blend ethylene-alpha-octylene graft copolymer and preparation method thereof
CN104628971A
Cited By
Multifunctional toughening agent and preparation method thereof
CN122255364A